2020
DOI: 10.1128/jcm.01764-19
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clostridioides difficile Infection-Related Complications and Treatment Patterns among Nucleic Acid Amplification Test-Positive/Toxin Enzyme Immunoassay-Negative Patients

Abstract: The addition of toxin enzyme immunoassay (EIA) to nucleic acid amplification tests, including PCR, creates challenges in the diagnosis and management of Clostridioides difficile infection (CDI). There are limited data in large cohorts, with discordant results, that is, PCR-positive/EIA-negative (PCR+/EIA−) results. We conducted a retrospective cohort study on all PCR+/EIA− adult inpatients and assessed CDI-related complications and clinical failure. We identified 240 individuals. Twenty-three (9.6%) patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…We compared the outcomes of patients with toxin EIA-negative, TC-positive, and toxin EIA-positive/TC-positive results to assess their clinical characteristics. The results showed no difference in clinical characteristics and outcomes, consistent with previous reports (28,29). However, research in the US reported that patients with positive NAAT-toxins had more complications and a higher blood leucocyte count than patients who were only positive for NAAT (30).…”
Section: Discussionsupporting
confidence: 90%
“…We compared the outcomes of patients with toxin EIA-negative, TC-positive, and toxin EIA-positive/TC-positive results to assess their clinical characteristics. The results showed no difference in clinical characteristics and outcomes, consistent with previous reports (28,29). However, research in the US reported that patients with positive NAAT-toxins had more complications and a higher blood leucocyte count than patients who were only positive for NAAT (30).…”
Section: Discussionsupporting
confidence: 90%
“…Many patients with discordant results on multistep screening testing have risk factors for C difficile and a clinical presentation consistent with CDI, and approximately 70% are treated with antibiotics for CDI . Compared with patients who have positive results on both C difficile multistep screening tests, patients with discordant results have less severe illness, reduced recurrence rates, and a lower mortality rate, although fulminant CDI can occur . Therefore, treatment should not be withheld if there is high clinical suspicion of CDI …”
Section: Test Characteristicsmentioning
confidence: 99%
“…Individuals with test results positive for GDH antigen and negative for toxin EIA can undergo NAAT to determine whether they have a toxigenic strain of C difficile . Many patients with discordant results on multistep screening testing have risk factors for C difficile and a clinical presentation consistent with CDI, and approximately 70% are treated with antibiotics for CDI . Compared with patients who have positive results on both C difficile multistep screening tests, patients with discordant results have less severe illness, reduced recurrence rates, and a lower mortality rate, although fulminant CDI can occur .…”
Section: Test Characteristicsmentioning
confidence: 99%
“…However, the sole reliance on molecular diagnostics without querying the host response will likely result in false positive diagnoses and unwarranted overtreatment. Recent literature underscores the potential for overtreatment despite this multi-step approach (17).…”
Section: Introductionmentioning
confidence: 99%